STRATEGI OPTIMALISASI RETRIBUSI PASAR DI PEMERINTAH KABUPATEN BANTUL - Ambarwati, Lilik (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2019)
The theme of this study is how the strategy planning in optimizing market levy in Bantul Regency. During 2012-2015, the levy achievement always exceeded the market target, but based on the potential data from Kepala Seksi Pendapatan in Kantor Pengelolaan Pasar, the specified target is too low, so that, the market levy still has potential to be optimized. Therefore, the aim of this study is to formulate the strategy to optimize market levy in Bantul Regency.The data used in this study was obtained from employees of the Kantor Pengelolaan Pasar both in the field and administration sector, also traders in Bantul district markets. The data was obtained through a questionnaire distributed to 34 employees of Kantor Pengelolaan Pasar, and interviews with market traders. The analysis mehod used is descriptive analysis and SWOT analysis.Based on the SWOT analysis, it is obtained the strategies for optimizing market levy in quadrant III by reducing the weaknesses to rise the opportunities. The implementation of the strategy, by the Kantor Pengelolaan Pasar, firstly by committing traders data validity, which is continued by collecting in an integrated system, that is a book keeping system. The officer made the routine administration after collecting, and traders who often do not pay the levy (in arrears) are required to pay the levy directly to BPD DIY.